Improving Outcomes Among Young Adults with type 1 diabetes: The D1 Now Randomised Pilot Study Protocol. Issue 9 (7th July 2020) - Casey, B.; Byrne, M.; Casey, D.; Gillespie, P.; Hobbins, A.; Newell, J.; Morrissey, E.; Dinneen, S. F.
Abstract: Background: Young adults (18‐25 years old) living with type 1 diabetes mellitus often have sub‐optimal glycaemic levels which can increase their risk of long term diabetes complications. Informed by health psychology theory and using a (public and patient involvement) young adult‐centred approach, we have developed a complex intervention, entitled D1 Now, to improve outcomes in this target group. The D1 Now intervention includes three components; 1) a support‐worker, 2) an interactive messaging system and 3) an agenda setting tool for use during clinic consultations. Aims: The aim of the D1 Now pilot study is to gather and analyse acceptability and feasibility data to allow us to (1) refine the D1 Now intervention, and (2) determine the feasibility of a definitive Randomised Control Trial (RCT) of the intervention. Methods: Diabetes clinics on the island of Ireland will be recruited and randomised to a D1 Now intervention arm or a usual care control arm. For a participant to be eligible they should be 18‐25 years old and living with type 1 diabetes for at least 12 months. Participant outcomes (influenced by a Core Outcome Set) include change in HbA1c, clinic attendance, number of episodes of severe hypoglycaemia and of diabetic ketoacidosis, diabetes distress, self‐management, quality of life and perceived level of control over diabetes; these will be will be measured at baseline and after 12 months follow‐up for descriptive statistics only. An assessment of treatment fidelity, a health economic analysis and a qualitative sub‐study will also be incorporated into the pilot study. ISRCTN (ref: ISRCTN74114336). Novelty Statement: What is already known? Young adults with type 1 diabetes often disengage from clinic attendance and may end up with sub‐optimal glycaemic levels and an increased risk of complications What this study has found We have developed a novel complex intervention, called D1 Now, which focuses on promoting engagement of young people with clinical services. We describe the protocol for a pilot cluster randomised controlled trial (RCT) evaluating the D1 Now intervention in 5 Diabetes Centres on the island of Ireland What are the clinical implications of the study? If the intervention proves feasible to deliver we plan to proceed to a definitive RCT with the aim of achieving improved long‐term outcomes for young adults